Prevalence and associated factors of metabolic body size phenotype in children and adolescents: A national cross-sectional analysis in China - Liu, Jieyu; Ma, Tao; Chen, Manman; Ma, Ying; Li, Yanhui; Gao, Di; Ma, Qi; Wang, Xinxin; Chen, Li; Zhang, Yi; Dong, Yanhui; Song, Yi; et al. (Frontiers in Endocrinology, 2022)
Background: Metabolic healthy obese (MHO) is a group of subjects with overweight/obesity who present a metabolic healthy profile, however, associated factors are complex and are far from completely understood. The aim of the current study was to estimate the prevalence of different metabolic body size phenotype, and investigate the associated factors in Chinese children and adolescents. Methods: A cross-sectional survey was conducted of 12346 children and adolescents aged 7-18 years from seven provinces in China in 2013. Anthropometric, blood pressure and biochemical measurements were obtained. A multi-component questionnaire covering demographic, neonatal, and lifestyle characteristics was administered. We compared the classification of metabolic body size phenotype based on three definitions. With metabolically healthy with normal-weight (MHNW) as a reference group, logistic regression analyses were used to estimate the potential effects of associated risk factors, with adjustment for age, sex, single-child status, and residence area. Results: The prevalence of MHNW, MHO, metabolically unhealthy with normal-weight (MUNW), and metabolically unhealthy overweight/obesity (MUO) phenotype was 68.6%, 2.0%, 26.4% and 3.0%, respectively. There were 39.3% MHO and 60.7% MUO among obese participants, 72.2% MHNW and 27.8% MUNW among those with normal weight. Compared to cardiometabolic risk factors (CMRFs) criteria and metabolic syndrome (MetS) components definition, the application of 2018 consensus-based definition may identify more children with abnormal cardiovascular risks, independent of weight status. Compared to younger children, older-aged adolescents were positively associated with higher risks of MUNW (OR=1.38, 95%CI=1.27-1.50) and MUO (OR=1.29, 95%CI=1.04-1.60), while factors positively associated with MHO were younger age, single-child status, urban residence, high birth weight, prolonged breastfeeding duration, parental overweight/obesity status, long screen time and less physical activity. Conclusion: There were still a high proportion of children and adolescents at high cardiometabolic risk in China. Our findings reinforce the need for cardiometabolic risk prevention in children and adolescents irrespective of their weight status, such as parental educational program and healthy lifestyle intervention.